PERSEPSI MASYARAKAT TERHADAP KESENIAN GUBANO BADIKIU DI DESA PARIT BARU KECAMATAN TAMBANG KABUPATEN KAMPAR - Damhuri "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Gubano Badikiu art is a traditional art must be kept. The Parit Baru desa people is a heir. They should know, care and maintain tradition art. To diagnose society perceptions about Gubano Badiku Art and what extend the Gubano Badikiu admitted by society. The society should find out Gubano Badikiu art deeply such as value and function as guidance and reference for people in daily life. The society should admit that Gubano Badikiu be able knit a communication when people usually see Gubano Badikiu art. In order Gubano Badikiu art always exist around people, so that the people should look for the way to solves the obstacle factors to lessen people interest. Toward Gubano Badikiu art. The ways to solve it involves all society, traditional leaders and goverment. The existence of cooperation directly from the parties concerned will have an impact to development and preservation.Keywords : Society Perceptions, tradition art, exist of Gubano Bdik